Self-healing polymeric gel via RAFT polymerization and Diels–Alder click chemistry. (9th July 2015) - Pramanik, Nabendu B.; Nando, Golok B.; Singha, Nikhil K.
Abstract: Tailor-made copolymers of furfuryl methacrylate (FMA) and butyl methacrylate (BMA) (PFMA-co-PBMA) were successfully synthesized by reversible addition fragmentation chain-transfer (RAFT) polymerization technique. The thermoreversible network was successfully achieved by Diels–Alder (DA) and retro-DA reaction between the furfuryl groups of PFMA part and a bifunctional maleimide cross-linker, bismaleimide. This process was studied by NMR spectroscopy, FT-IR spectroscopy, differential scanning calorimetry (DSC) and nano-indentation analysis. DSC analysis was used to determine of the endothermic retro-DA reaction in copolymer-DA adduct. In this investigation self-healing property of the above cross-linked material was demonstrated by monitoring the repair of a scratch in the copolymer film upon heating and cooling. This was analyzed by scanning electron microscopy (SEM). Graphical abstract: Highlights: Copolymers of FMA and BMA were prepared via RAFT polymerization. DA reaction was used to prepare cross-linked polymeric gel. The polymeric gel showed endotherm and exotherm peak in DSC analysis. Nano-indentation analysis was used to study the cross-linking behavior. Cross-linked gel showed self-healing characteristics, studied by SEM analysis.